2011
DOI: 10.1021/ja1099209
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation-Induced Chemical Reactions: Acid Dissociation in Growing Water Clusters

Abstract: Understanding chemical reactivity at ultracold conditions, thus enabling molecular syntheses via interstellar and atmospheric processes, is a key issue in cryochemistry. In particular, acid dissociation and proton transfer reactions are ubiquitous in aqueous microsolvation environments. Here, the full dissociation of a HCl molecule upon stepwise solvation by a small number of water molecules at low temperatures, as relevant to helium nanodroplet isolation (HENDI) spectroscopy, is analyzed in mechanistic detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
77
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 86 publications
1
77
0
Order By: Relevance
“…The D 0 of the fully deuterated isotopologue is calculated to be 1476 ± 3 cm −1 , which we hope will stand as a benchmark for future experimental work. [1][2][3][4][5][6] and theoretical [7][8][9][10][11] studies. The high interest in these complexes is due to their impact on atmospheric chemistry, specifically their role in ozone depletion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The D 0 of the fully deuterated isotopologue is calculated to be 1476 ± 3 cm −1 , which we hope will stand as a benchmark for future experimental work. [1][2][3][4][5][6] and theoretical [7][8][9][10][11] studies. The high interest in these complexes is due to their impact on atmospheric chemistry, specifically their role in ozone depletion.…”
mentioning
confidence: 99%
“…[16][17][18][19][20][21][22] However, recent high level quantum mechanical studies predict the coexistence of non-ionized clusters at the four-monomer limit. 8,10 The complexity of the problem is even more apparent from the lack of experimental consensus on the identification of the ionized cluster. 4,23 A building block to understanding the clusters at the four-water limit and beyond is a detailed knowledge of even smaller HCl-H 2 O clusters, the first of which is the HCl-H 2 O dimer.…”
mentioning
confidence: 99%
“…12,13,60 As shown in Fig. 3 very little energy drift was seen in both simulations up to 1.2 and 2.5 ps; maintaining energy conservation during proton shuttling. Prior AIMD simulations (at the less accurate DFT+GGA level) of this "smallest acid droplet" have shown that adding a fourth water to an HCl(H 2 O) 3 cluster results in a spontaneous dissociation of the proton into the water.…”
mentioning
confidence: 68%
“…Prior AIMD simulations (at the less accurate DFT+GGA level) of this "smallest acid droplet" have shown that adding a fourth water to an HCl(H 2 O) 3 cluster results in a spontaneous dissociation of the proton into the water. 12,13 In our calculations it was found that the initial potential energy of the cluster was very sensitive to the basis set size. The cluster dissociates almost immediately when using the smaller basis set.…”
mentioning
confidence: 76%
See 1 more Smart Citation